The Analysis of Environmental Metaphor Found in Holmes and Ammer’s Collection: A Cognitive Linguistics Approach - Trisha Endah Setiawati; I Nengah Laba; I Gede Neil P. Wardhana (LPPM Universitas Dhyana Pura, 2023)
This study aimed to find out the category and the mapping of the source and target domains of the environmental metaphors in Holmes and Ammer’s metaphor collection. The cognitive linguistics approach used a descriptive qualitative approach to find out the metaphors. Lakoff and Johnson’s conceptual metaphor theory was used in this study. To conceptualise the relationships between the source and target domains and their meaning, the mapping was used to explain it. The study found nine data: four belong to structural metaphors, three belong to orientational metaphors, and two from ontological metaphors. The environmental category found were animals, plants, oceanic, weather, and terrestrial ecosystem.